Positionality and transformative knowledge in conducting 'feminist' research on empowerment in Bangladesh - Nazneen, Sohela; Sultan, Maheen (© 2013 Elsevier Ltd., 2016)
This article was published in Women's Studies International Forum [ © 2013 Elsevier Ltd. ] and the definite version is available at: http://doi.org/10.1016/j.wsif.2013.11.008 The Article's website is at: http://www.sciencedirect.com/science/article/pii/S0277539513002082